Mechanistic aspects of carotenoid health benefits – where are we now?. Issue 2 (31st December 2021) - Bohn, Torsten; Bonet, M. Luisa; Borel, Patrick; Keijer, Jaap; Landrier, Jean-Francois; Milisav, Irina; Ribot, Joan; Riso, Patrizia; Winklhofer-Roob, Brigitte; Sharoni, Yoav; Corte-Real, Joana; van Helden, Yvonne; et al.
Abstract: Dietary intake and tissue levels of carotenoids have been associated with a reduced risk of several chronic diseases, including cardiovascular diseases, type 2 diabetes, obesity, brain-related diseases and some types of cancer. However, intervention trials with isolated carotenoid supplements have mostly failed to confirm the postulated health benefits. It has thereby been speculated that dosing, matrix and synergistic effects, as well as underlying health and the individual nutritional status plus genetic background do play a role. It appears that our knowledge on carotenoid-mediated health benefits may still be incomplete, as the underlying mechanisms of action are poorly understood in relation to human relevance. Antioxidant mechanisms – direct or via transcription factors such as NRF2 and NF-κB – and activation of nuclear hormone receptor pathways such as of RAR, RXR or also PPARs, via carotenoid metabolites, are the basic principles which we try to connect with carotenoid-transmitted health benefits as exemplified with described common diseases including obesity/diabetes and cancer. Depending on the targeted diseases, single or multiple mechanisms of actions may play a role. In this review and position paper, we try to highlight our present knowledge on carotenoid metabolism and mechanisms translatable into health benefits related to several chronic diseases.